Anti‐M3 muscarinic acetylcholine receptor antibodies in patients with primary biliary cirrhosis. Issue 14 (13th May 2014) - Tsuboi, Hiroto; Ohira, Hiromasa; Asashima, Hiromitsu; Tsuzuki, Sayaka; Iizuka, Mana; Matsuo, Naomi; Kondo, Yuya; Matsumoto, Isao; Sumida, Takayuki
<x xml:space="preserve">Abstract</x> Aim M3 muscarinic acetylcholine receptor (M3R) is expressed in biliary tracts as well as in exocrine glands. It is reported that some patients with primary biliary cirrhosis (PBC) carry autoantibodies against M3R. The aim of this study is to clarify the presence, potential use as diagnostic marker and clinical roles of anti‐M3R antibodies in PBC. Methods We synthesized peptides encoding the extracellular domains of human‐M3R, including the N‐terminal region, the first, second and third extracellular loops. Antibodies against these regions were examined by peptide‐based enzyme‐linked immunoassay in sera of 90 patients with PBC and 40 with chronic hepatitis C (CHC), 21 with non‐alcoholic steatohepatitis (NASH), 10 with primary sclerosing cholangitis (PSC), 14 with obstructive jaundice, 10 with drug‐induced liver injury and 42 healthy controls. Results Antibodies to the N‐terminal, first, second and third loop were detected in 90.0% (81/90), 73.3% (66/90), 76.7% (69/90) and 66.7% (60/90) of PBC, in 67.5% (27/40), 10.0% (4/40), 67.5% (27/40) and 27.5% (11/40) of CHC, in 85.7% (18/21), 9.5% (2/21), 4.8% (1/21) and 57.1% (12/21) of NASH, in 60.0% (6/10), 20.0% (2/10), 60.0% (6/10) and 60.0% (6/10) of PSC, in 100.0% (14/14), 0% (0/14), 64.3% (9/14) and 78.6% (11/14) of obstructive jaundice, in 100.0% (10/10), 0% (0/10), 30.0% (3/10) and 10.0% (1/10) of drug‐induced liver injury, and in 4.8% (2/42), 7.1% (3/42), 2.4% (1/42) and 2.4% (1/42) of the controls, respectively. Conclusion A high frequency of PBC carried anti‐M3R antibodies. Anti‐M3R antibodies against the first loop of M3R are a potentially useful diagnostic marker for PBC.